2018
DOI: 10.1111/dgd.12564
|View full text |Cite
|
Sign up to set email alerts
|

Melanophore multinucleation pathways in zebrafish

Abstract: In zebrafish, apart from mononuclear melanophores, bi- and trinuclear melanophores are frequently observed; however, the manner in which multinucleation of these cells occurs during fish development remains unknown. Here, we analyzed the processes underlying multinucleation of zebrafish melanophores. Transgenic zebrafish in which melanophore nuclei were labeled with a histone H2B-red fluorescent reporter protein were used to evaluate the distribution of mono-, bi-, and trinuclear melanophores in both the trunk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…If planar areas of concentrated melanin granules are assumed spherical, then euthyroid melanophores had on average ~1.7 x the total melanin content of hypothyroid melanophores. (Data in supplementary file Figure 5—source data 1) ( D ) Fully differentiated melanophores of zebrafish are often binucleate (Usui et al, 2018). Left panel shows a binucleate stripe melanophore in a euthyroid fish (12 SSL).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If planar areas of concentrated melanin granules are assumed spherical, then euthyroid melanophores had on average ~1.7 x the total melanin content of hypothyroid melanophores. (Data in supplementary file Figure 5—source data 1) ( D ) Fully differentiated melanophores of zebrafish are often binucleate (Usui et al, 2018). Left panel shows a binucleate stripe melanophore in a euthyroid fish (12 SSL).…”
Section: Resultsmentioning
confidence: 99%
“…Finally we examined multinucleation, a condition linked to increased cell survival and size (Orr-Weaver, 2015; Usui et al, 2018). In euthyroid fish, ~20% of melanophores were binucleate near the onset of adult melanophore differentiation but >50% were binucleate by juvenile stages, confirming an overall increase in binucleation with somatic stage and melanophore age (Figure 5—figure supplement 1E).…”
Section: Resultsmentioning
confidence: 99%
“…Genes expressed during terminal differentiation of melanophores from euthyroid fish were expressed at lower levels in melanophores of hypothyroid fish, suggesting an impediment to maturation in the absence of TH (Figure 5A). Cytologically, mature melanophores of euthyroid fish are frequently binucleate-a condition associated with increased survival and larger size (Orr-Weaver, 2015;Usui et al, 2018)-whereas we found that melanophores of hypothyroid fish were frequently mononucleate, suggesting they had failed to complete differentiation (Figure 5B and C). Given these findings and an earlier observation that melanophores of euthyroid fish fail to divide whereas those of hypothyroid fish continue to do so (McMenamin et al, 2014), we hypothesized that TH promotes a terminally differentiated state of cellular senescence.…”
Section: Th Promotes a Melanophore Maturation Program And Drives Cellmentioning
confidence: 79%
“…The largest cluster (#3) contains 41% of the genes and represents loci expressed late in pseudotime of euthyroid melanophores but downregulated in hypothyroid melanophores, identifying novel candidate genes for roles in melanophore maturation (see Table 6, in which published melanophore-related genes are highlighted ) (Baxter et al, 2018). (B) Fully differentiated melanophores of zebrafish are often binucleate (Usui et al, 2018) as, shown in vivo for a stripe melanophore isolated from a euthyroid fish (12 SSL). By contrast, melanophores of hypothyroid fish at equivalent stages were often mononucleate.…”
Section: Figure 2-figure Supplement 4 Distinct Domains Of Gene Exprmentioning
confidence: 99%
“…This observation is consistent with high resolution photographs of black background-adapted dorsal melanophores reported previously (Logan et al, 2006). Several of these transparencies were in close proximity ( Figure 2D ); zebrafish melanophores have been frequently shown to be multinucleated (Usui et al, 2018). In contrast to the flattened, diffuse melanin in the stripes, pigment units not associated with the four larval stripes appeared to have a globular, condensed morphology.…”
Section: Resultsmentioning
confidence: 98%